Influence of microbiological transglutaminase on the sensory properties of burgers of minced hake (Merluccius hubbsi) (INNOTEC, 2013)
Burgers of minced hake (Merluccius hubbsi) were prepared with the addition of microbial transglutaminase, in order to improve sensorial properties and hence to develop a fishery product that encourage the consumption of fish in Uruguay. The effect of the enzyme was evaluated by sensory and instrumental analysis. Three types of hamburgers were prepared: two with transglutami-nase (0,5% and 1,0%) and a control sample without enzyme. A panel of six trained sensory assessors identified the most relevant descriptors and provided the corresponding ratings on an individual basis. Instrumental texture measurements were performed with a texture analyzer TA.XT2i. The obtained results suggest that the addition of microbial transglutaminase substantially improved the appearance, texture and flavor of the product. An innovating fishing product was obtained with features that can be very attractive to Uruguayan consumers.
Keywords: Burgers; minced hake; transglutaminase; sensorial evaluation